Assessment of single and combined effects of two pharmaceuticals in non-target species: evaluation of possible interactions - Daniel, David Matias (2020)
Increase in life quality is partially linked to the use of pharmaceuticals. These are used in several areas and represent a great advancement in disease treatment and population welfare. Nevertheless, the increase in pharmaceutical usage lead to an increase in the detection of these compounds in the water courses. This happens because wastewater treatment plants are unable to fully remove these contaminants. From the most detected classes in the environment are non-steroid anti-inflammatory drugs (NSAIDs). NSAIDs are used as analgesics, anti-inflammatory and antipyretic. An example of this class is salicylic acid (SA) which similar to this class acts by inhibiting the activity of cyclooxygenase (COX). Which, in its turn is responsible for the synthesis of inflammatory mediators. From an environmental point of view, another class of interest, is that of the diuretics, particularly the subgroup of carbonic anhydrase inhibitors. Pharmacologically, this class acts by inhibiting the activity of enzyme carbonic anhydrase (CA). This enzyme is responsible for acid-base balance in organisms as well as key processes such as carbon obtention in plants, calcium mobilization in arthropods among others. The goal of this work was to evaluate the effects of environmental realistic concentrations of ACZ and SA (individually and in mixture) in non-target species (namely Lemna gibba, Mytilus spp.,and Phorcus lineatus) using biomarkers (enzymes such as CA, COX), photosynthetic pigments and biometrics. Photosynthetic pigments from L. gibba showed ACZ capacity to inhibit their synthesis. Nevertheless, in mixture with SA, these effects were reversed, showing the phyto-protection capacity of SA. In organisms from the genus Mytilus spp. exposure to ACZ display the capacity of this pharmaceutical to inhibit CA, especially in gills. When in mixture, the decrease in COX activity suggest ACZ modulates SA excretion. Finally, in organisms from P. lineatus the here tested pharmaceuticals did not caused any straightforward pattern in evaluated enzymes. In conclusion, pharmaceuticals can have different effects in different organisms. Being pharmaceutical mixture here tested capable of being beneficial to plants (by reversed photosynthetic pigment reduction) or be harmful in mussels (increased inhibition of COX activity).